An improved curve‐shaped droop control method for islanded microgrid under heavy load disturbance. (11th November 2021) - Zhang, Tengfei; Zhang, Bo; Dou, Chunxia; Peng, Chen; Ma, Fumin; Yue, Dong
Summary: Due to lack of support from the main grid, the problem of frequency over‐limitation is easily caused during heavy load disturbance occurs in the islanded microgrid (MG). For this reason, an improved curve‐shaped droop control strategy, which is composed by virtual synchronous generator (VSG) and an improved droop control, is designed to ensure the frequency stable of the MG system. In the contributed strategy, when the frequency of MG is changed within the normal range, the VSG control will be adopted to maintain the stability of the output power and frequency, this method can ensure that the frequency can be adjusted within the stable range rapidly; when the frequency deviation is serious, the proposed strategy will select the improved droop control strategy to ensure the output power equals to the load demand, and to ensure that the controlled frequency cannot lower than the minimum value. In addition, in order to suppress the voltage deviation and the system oscillation caused by the switching of the control methods, a voltage synchronization control strategy is also proposed, which can realize the smooth switching of the two control strategies and guarantees the voltage stable of the MG system. The effectiveness of the proposed methods is verified by simulation experiments via matlab/Simulink software. Abstract : When the frequency of MG is within the normal range, DGs will be controlled by VSG controller, and the frequency can smoothly slide to a new stable point under small disturbance; otherwise, the controller will be switched to the improved droop control to ensure the frequency within the allowable range.